Carbon pricing, border adjustment and climate clubs: An assessment with EMuSe - Anne Ernst; Natascha Hinterlang; Alexander Mahle; Nikolai Stähler (Deutsche Bundesbank, 2022)
In a dynamic, three-region environmental multi-sector general equilibrium model (called EMuSe), we find that carbon pricing generates a recession initially as production costs rise. Benefits from lower emissions damage materialize only in the medium to long run. A border adjustment mechanism mitigates but does not prevent carbon leakage, but it 'protects' dirty domestic production sectors in particular. From the perspective of a region that introduces carbon pricing, the downturn is shorter and long-run benefits are larger if more regions levy a price on emissions. However, for non-participating regions, there is no incremental incentive to participate as they forego trade spillovers from carbon leakage and face higher production costs along the transition. In the end, they may be better off not participating. Because of the costly transition, average world welfare may fall as a result of global carbon pricing unless 'the rich' assist 'the poor'.
Keywords: E32; E50; E62; H32; Q58; 330; Carbon Pricing; Border Adjustment; Climate Clubs; International Dynamic General Equilibrium Model; Sectoral Heterogeneity; Input-Output Matrix